Pendidikan Kesetaraan Gender dalam Perspektif Al-Qur’an - Azis, Miftakul (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
In changing the view of Muslims on gender, it is necessary to have a broad scientific insight and taken from clear sources, this aims to ensure that the understanding obtained corresponds to what is expected, namely the existence of gender equality. Based on the focus and formulation of the problem, the purpose of this paper is to know the education of gender equality in the perspective of the Quran.The research scope is more focused on education, the research method used by the author is a qualitative research method, using the approach libreria researches (library research). The object of study in this paper is literatures such as books and journals that have a correlation with the discussion in this paper, namely gender equality education in the perspective of the Qur'an. In the modern era such as today, it should be that as a human being both men and women can be broader in thinking and not conflating and limiting each other, because basically the Qur'an views men and women as equal based on their abilities and duties each, and none Discernment in God's sight, except for his fear. In the Islamic world, education is very important for the individual, this can be seen from the many verses of the Qur'an and the hadith of Pendidikan Kesetaraan Gender Dalam Perspektif Al-Qur’an the prophet that encourage Muslims to seek knowledge and develop the skills of both men and women.